2023
DOI: 10.1038/s41419-023-05599-1
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be a fat burner, that is the question for cpt1c in cancer cells

Abstract: There is an urgent need to identify reliable genetic biomarkers for accurate diagnosis, prognosis, and treatment of different tumor types. Described as a prognostic marker for many tumors is the neuronal protein carnitine palmitoyltransferase 1 C (CPT1C). Several studies report that CPT1C is involved in cancer cell adaptation to nutrient depletion and hypoxia. However, the molecular role played by CPT1C in cancer cells is controversial. Most published studies assume that, like canonical CPT1 isoforms, CPT1C is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…CPT1C has been shown to exacerbate the severity of GC previously. 5–7 To characterize the role of CPT1C in the tumor microenvironment (TME), we analyzed the scRNA-seq data encompassing 118,027 cells from 40 samples of 29 GC patients and divided them into 9 distinct categories based on their transcriptional features ( Figure 1(a) ). Next, we assessed the expression of CPT1C across these cell types and observed that some subpopulations of fibroblasts exhibited a remarkably high expression of CPT1C, followed by endothelial and smooth muscle cells ( Figure 1(b,c) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CPT1C has been shown to exacerbate the severity of GC previously. 5–7 To characterize the role of CPT1C in the tumor microenvironment (TME), we analyzed the scRNA-seq data encompassing 118,027 cells from 40 samples of 29 GC patients and divided them into 9 distinct categories based on their transcriptional features ( Figure 1(a) ). Next, we assessed the expression of CPT1C across these cell types and observed that some subpopulations of fibroblasts exhibited a remarkably high expression of CPT1C, followed by endothelial and smooth muscle cells ( Figure 1(b,c) ).…”
Section: Resultsmentioning
confidence: 99%
“… 4 CPT1C, an atypical isoform with limited catalytic activity, stands out due to its role as a nutrient sensor regulating cancer cell metabolic reprogramming in response to the dynamic TME. 5 In GC, studies have highlighted the association of elevated CPT1C expression with unfavorable prognosis, enhanced cancer cell proliferation, and distant metastasis. 6 , 7 However, whether CPT1C correlates with any key components in TME and its potential implication in immunomodulation are largely unknown in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Several findings have shown that CPT1C is localized in the endoplasmic reticulum of stem cells and neurons but not in the mitochondria [ 55 , 56 ]. CPT1C has also been detected in mitochondria-associated membranes and microsomes in MCF7 cells [ 57 ]. Our data indicated that CPT1C was present in mitochondria in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, CPT1C expression is known to regulate lipid metabolic reprograming and cell adaptation to environmental stressors. In neurons, it regulates metabolism and function by interacting with proteins involved in the regulation of lipid metabolism, Golgi-mediated secretory transport, and the endolysosomal system [ 75 ].…”
Section: Discussionmentioning
confidence: 99%